Evolutionary landscape of plant chalcone isomerase-fold gene families - Luo, Kai-yong; Wang, Shi-ping; Yang, Ling; Luo, Sen-lin; Cheng, Jia; Dong, Yang; Ning, Ya; Wang, Wei-bin (Frontiers in Plant Science, 2025)
Flavonoids are crucial for plant survival and adaptive evolution, and chalcone isomerase (CHI) genes serve as key rate-limiting gene in the flavonoid biosynthesis pathway. It is important for plant adaptive evolution to comprehensively study the evolution and diversity of the CHI gene families. However, the CHI gene families in many plant lineages remain elusive. This study systematically identified CHI genes from 259 species including algae, bryophytes, ferns, gymnosperms, and angiosperms. A total of 1,738 CHI gene family members were discovered. We analyzed the diversity, distribution trajectory, and the driving forces of gene duplication during the evolution of the plant lineages. The present study is the first to identify potential type II and type IV CHI genes in the extant liverwort model species Marchantia polymorpha. The distribution pattern of CHI genes across the plant kingdom reveals that the origin of type II CHI can be traced back to the last common ancestor of bryophytes and vascular plants, and type III CHI may represent the ancestral form of the CHI gene family. The identification of conserved motifs showed significant differences in motif distribution among different CHI gene types. It was found that the drivers of gene duplication varied across plant lineages: dispersed duplications (DSD) were predominant in algae and bryophytes, whole-genome duplication (WGD) was the main driver in basal angiosperms and monocots, while tandem duplications (TD) predominating in eudicots. Structural clustering analysis demonstrated the 3-layer sandwich structure in the CHI-fold proteins remained conserved in the central region, while repeated loss of N-terminal sequences contributed to structural diversity. This study provides a deeper understanding of the evolution and diversity of the CHI-fold proteins and lays a theoretical foundation for further studies of their function and the identification of new functional CHI genes.